2022
DOI: 10.1093/jamia/ocac209
|View full text |Cite
|
Sign up to set email alerts
|

Training digital natives to transform healthcare: a 5-tiered approach for integrating clinical informatics into undergraduate medical education

Abstract: Expansive growth in the use of health information technology (HIT) has dramatically altered medicine without translating to fully realized improvements in healthcare delivery. Bridging this divide will require healthcare professionals with all levels of expertise in clinical informatics. However, due to scarce opportunities for exposure and training in informatics, medical students remain an underdeveloped source of potential informaticists. To address this gap, our institution developed and implemented a 5-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Moreover, Echelard et al [13] conducted a scoping review investigating current DH training for medical students, and suggested that the broad concept of DH should be studied at the same time as more specific subjects such as programming. To address this issue, the CBIS workshop gathered the most important skills expected of professionals involved with DH, facilitating the formation of a standardized curriculum, as has also been done in other initiatives worldwide [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Echelard et al [13] conducted a scoping review investigating current DH training for medical students, and suggested that the broad concept of DH should be studied at the same time as more specific subjects such as programming. To address this issue, the CBIS workshop gathered the most important skills expected of professionals involved with DH, facilitating the formation of a standardized curriculum, as has also been done in other initiatives worldwide [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“… 82 Further work is needed to explore the effectiveness of this. 82 Hare et al, 83 meanwhile suggested a tiered informatics curriculum design for medical education, which included different levels of depth within courses that students could opt into, ranging from shorter crash courses to longer fellowships based on their preferences. Successful implementation, however, depends on careful planning, resource allocation, and collaboration with healthcare institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Successful implementation, however, depends on careful planning, resource allocation, and collaboration with healthcare institutions. 83 …”
Section: Discussionmentioning
confidence: 99%
“…Domains of clinical informatics (CI)-such as telemedicine, 1 large language models, 2 and artificial intelligence (AI) 3 -have touched the lives of medical trainees in recent years. Now more than ever, it is crucial to unlock the potential of CIrelated education in undergraduate medical education (UME) [4][5][6][7][8][9][10] and graduate medical education (GME). Prior literature regarding medical students suggests that there is interest in CI but a lack of clarity around opportunities for CI training, mentorship, and careers.…”
Section: Clinical Informatics At the Graduate Medical Education Levelmentioning
confidence: 99%